Some Dimensions of Farmers'-Pastoralists' Conflicts in the Nigerian Savanna - Mayowa Fasona; Eniola Fabusoro; Comfort Sodiya; Vide Adedayo; Felix Olorunfemi; Peter Omu Elias; John Oyedepo; Grace Oloukoi (Journal of Global Initiatives, 2016)
The savanna ecosystem covers about 48.5% of Nigeria’s land area. It is a national common for intensive cropping and extensive grazing. Fierce competition for land and water resources among the crop farmers and pastoralists is a common feature. This article shares insights from two separate, but linked, studies conducted in the Nigerian savanna on the livelihood and food security of the local peasant farming communities and the vulnerability of the settled Fulani agro-pastoralists’ livelihoods. Household interviews, focus group discussions, and key informant interviews were employed among both the farming and agro-pastoralist communities. 191 respondents in 11 local farming communities and 201 households in 40 Fulani sub-communities (pastoral family steads locally referred to as “gaa”) were sampled in Ogun, Oyo, and Kwara States. Evidence from the studies suggests that poor resource governance arrangment is a key factor of farmer-pastoralist conflict. Both the farmers and pastoralists are sufficiently aware of the threat of clashes to human insecurity in the region. Some of the communities are taking steps to build confidence and improve relationships with the agro-pastoralist communities. On the other hand, the Fulanis also have conflict resolution measures and collective actions to reach out to their host farming communities. The role of the government has not been very encourging. More concrete and proactive measures are required to improve resource governance in order to de-escalate the current levels of resource conflicts in the savanna.